Micronucleus analysis in buccal swabs of paddy farmers from the East Coast of Malaysia - Asmah Hamid,; Kholilul Syafiq Baharuddin,; Nor Fadilah Rajab,; Syarif Husin Lubis,; Ismarulyusda Ishak,; Nur Zakiah Mohd Saat,; Nihayah Mohammad,; Mohd Jamil Mohd Rafaai,; Mohd Nazir Nasrom,
Pesticide exposure may cause genotoxic effects by inducing the formation of micronucleus (Mn). Mn are fragments of chromosomes that remains after cells division. The increase in Mn may increase the risk of cancer formation. Our study aimed to determine the effects of lifestyle and pesticide exposure on the formation of Mn in epithelial cells from buccal swabs among paddy farmers in Malaysia. About 40 farmers who were exposed to pesticides were chosen as subjects and 30 personnels whose not directly exposed to pesticides, were chosen as the control group. Demographic and anthropometric data were obtained from questionnaires developed. Analysis of Mn formation was done using Giemsa staining (10% v/v) and the frequency of Mn formation was scored from 1000 cells per sample. Kruskal-Wallis test done between Mn frequency with age group showed a significant increase (p < 0.05) in Mn frequency in farmers as compared to the control in the age group of 30-39 , 40-49 years, and 50-59 years. Significant increased (p < 0.05) were observed between Mn frequency groups of normal BMI, pre-obese, and grade 1 obese as compared to control. Significant increase of Mn frequency (p < 0.01) was also seen among smokers and farmer’s group (15.39 ± 3.34) as compared to controls (4.76 ± 1.26). The maximum numbers of Mn found in farmers are 7 Mn per cell whereas for control group is only 3 Mn. However, most farmers had only 1 Mn (81.75 ± 6.42%) and 2 Mn (15.28 ± 5.14%). Mn frequency with the duration of exposure to pesticides in a month and the use of PPE revealed no significant difference (p = 0.27). In conclusion, the increased frequency of Mn was influenced by age, gender, BMI and smoking status of farmers besides commonly repeated duration of exposures and the use of PPE. Further studies are needed to analyze the causes of an increased in Mn among farmers.